The Transition in 2nd of Baccalaurate’s textbooks. The case of Galicia - Lozano Ramírez, Amado Tierra (Clio. History and History Teaching, 2023)
The Transition constitutes a key stage in the configuration of the historical present of the students and their understanding, therefore, their inclusion in the teaching-learning process acquires a particular interest. The objective of this paper is to analyze how the teaching of this historical stage is articulated in textbooks. The study framework is limited to the manuals of the 2nd year of Baccalaureate in Galicia, on which a didactic and historiographical analysis is carried out. The study demonstrates, in the didactic field, a general lack of adaptation to the particularities of the History of the present, without betting on meaningful learning. In the historiographical, the same lack is revealed, as well as the hegemony of the traditional story, characterized by consensus and political, personalist, deterministic and positive History, without problematization or allusion to alternative proposals, conflict or the correlation of forces.